Corrosion behavior and biocompatibility evaluation of a novel zinc‐based alloy stent in rabbit carotid artery model. Issue 6 (8th November 2018) - Lin, Song; Ran, Xiaolin; Yan, Xinhao; Yan, Wenhua; Wang, Qilong; Yin, Tieying; Zhou, Jack G; Hu, Tingzhang; Wang, Guixue
Abstract: Zinc (Zn) and its alloys have been proved to be promising candidate materials for biodegradable cardiovascular stents. In this study, a novel extruded Zn–0.02 Mg–0.02Cu alloy was prepared. Compared with pure Zn, the Zn‐based alloy showed higher mechanical properties, and the Zn‐based alloy could significantly accelerate Zn 2+ release, reaching 0.61 ± 0.11 μg/mL at 15 days of immersion. In vitro biocompatibility studies demonstrated that the Zn‐based alloy had excellent cytocompatibility and hemocompatibility, including low hemolysis rate (0.63 ± 0.12%) and strong inhibitory effect on platelet adhesion. Subsequently, the Zn‐based alloy stent was implanted into the left carotid arteries of New Zealand white rabbits for 12 months. All the rabbits survived without any adverse clinical events, and all the stented arteries were patent during the study period. Rapid endothelialization at 1 week of implantation was observed, suggesting a low cytotoxicity and thrombosis risk. The stent corroded slowly and no obvious intimal hyperplasia was observed for 6 months, after which corrosion accelerated at 12 months. In addition, no obvious thrombosis and systemic toxicity during implantation period were observed, indicating its potential as the backbone of biodegradable cardiovascular stents. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1814–1823, 2019.